IMPLEMENTASI PROGRAM MITIGASI BENCANA PADA SEKOLAH DASAR KAWASAN ZONA MERAH KECAMATAN PADANG UTARA - riveldasali putri; Syafri Anwar (JURNAL BUANA, 2019)
the purpose of this research to find the implementation of disaster mitigation program in the red zone primary school in Padang Utara District. Descriptive research type with a mixed method (mixing method). Population research primary school in the red zone Padang Utara District. Research samples consisted of school samples and respondents samples. The respondents consisted of 6 principals, 6 teachers and 90 students. Research data obtained through interview techniques and questionnaires to students From the results of the study showed (1). Implementation of the disaster mitigation program in six primary schools implementation is still a lot of shortcomings. (2) based on the results of the study found several obstacles where in school research schools do not have a special budget program for the implementation of mitigation or disaster risk reduction efforts, causing the disaster mitigation program in the elementary school of the red zone in Padang Utara sub-district has not been implemented properly. (3). Based on the research questionnaire, it was found that the level of students' knowledge of the implementation of disaster mitigation was in the high category, namely (73.97%). Keywords: Mitigation of disasters, earthquake and tsunami disasters